2017
DOI: 10.1007/s10068-017-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pH indicator composed of high moisture-absorbing materials for real-time monitoring of chicken breast freshness

Abstract: A colorimetric bromocresol purple dye-based pH-responsive indicator was developed to monitor the quality of chicken breast meat by direct surface contact. To prevent direct contact of the dye with the chicken breast and to improve its color change sensitivity, it was immobilized with polyvinyl alcohol and a high-absorbance material. The color of the pH indicator changes from yellow to blue and finally purple to indicate spoilage, which can be easily detected by the naked eye. The asprepared pH indicator exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…It can catalyze reversible phosphorylation and participate in the carbohydrate metabolism pathway. 5,40 The expression of ⊍-1,4-glucan phosphorylase significantly changed during storage from 0 week to 2 week, which indicated that the sugar metabolism of prepared chicken breast had changed. At the second week of storage, the quality of chicken breast deteriorated and produced a bad smell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can catalyze reversible phosphorylation and participate in the carbohydrate metabolism pathway. 5,40 The expression of ⊍-1,4-glucan phosphorylase significantly changed during storage from 0 week to 2 week, which indicated that the sugar metabolism of prepared chicken breast had changed. At the second week of storage, the quality of chicken breast deteriorated and produced a bad smell.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies mainly focused on the storage, preservation technology and appearance index of quality change of the prepared chicken breast. [5][6][7] To our best knowledge, there is currently little systematic research about the quality deterioration mechanism of prepared chicken breast. Prepared chicken breast deterioration is a complex biochemical process, of which protein change is one of the main features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH measured with a portable pH meter averaged 5.63 ± 0.12 (range 5.36–5.98). The pH is an important indicator of microbial growth and changes in metabolite levels originating from food spoilage and protein degradation (Kim et al 2017). Our pH data showed that storage conditions can ensure consistency among samples.…”
Section: Figurementioning
confidence: 99%
“…Various automatic systems for food tracking have been proposed and developed, acquiring different sensory data to track the changes in food freshness during storage [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The conventional indicators used in these works were CO 2 concentration, food pH level, and meat color, which are intimately related to food freshness.…”
Section: Introductionmentioning
confidence: 99%